2010
DOI: 10.1103/physrevlett.105.123202
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Laser-Assisted Electron-Atom Scattering in Femtosecond Intense Laser Fields

Abstract: Laser-assisted electron scattering (LAES) in a femtosecond near-infrared intense laser field was observed through the scattering of 1 keV electrons by xenon atoms. The intensities, angular distributions, and laser polarization dependence of the observed LAES signals for the energy gain (+ℏω) and energy loss (-ℏω) processes were interpreted well by numerical simulations. As an application of this femtosecond-LAES process, a new method of time-resolved gas electron diffraction for probing geometrical change of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 17 publications
1
88
0
Order By: Relevance
“…The second condition ensures that one can observe both the low-energy and the high-energy plateaus in LAES spectra. Thus, for example, in the recent experiments of Kanya et al [32] neither of these two conditions for observing the effects we predict are fulfilled: u p /(hω) = 6.8 × 10 −2 and E/u p = 9.4 × 10 3 . On the other hand, analysis of the analytic results (6) and (9) shows that over the energy interval 0.2u p < E < u p the propagation factor W (p,p n ) decreases with increasing λ and I as W ∼ λ −4.2 I −c , where c = 0.75 for η = 0 and c = 0.45 for |η| = 1 (e.g., cf.…”
Section: Requirements For Experimental Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second condition ensures that one can observe both the low-energy and the high-energy plateaus in LAES spectra. Thus, for example, in the recent experiments of Kanya et al [32] neither of these two conditions for observing the effects we predict are fulfilled: u p /(hω) = 6.8 × 10 −2 and E/u p = 9.4 × 10 3 . On the other hand, analysis of the analytic results (6) and (9) shows that over the energy interval 0.2u p < E < u p the propagation factor W (p,p n ) decreases with increasing λ and I as W ∼ λ −4.2 I −c , where c = 0.75 for η = 0 and c = 0.45 for |η| = 1 (e.g., cf.…”
Section: Requirements For Experimental Measurementsmentioning
confidence: 99%
“…In recent experiments on LAES [32][33][34][35] the observation of n-photon absorption or emission was limited to n = 2 owing to the very weak LAES signal for high n. We emphasize that in order to observe higher nonlinear multiphoton effects in LAES, such as the plateaulike structures, the following criteria for choosing the laser field parameters and the values of the incident electron energy should be satisfied. On the one hand, the conditions u p /(hω)…”
Section: Requirements For Experimental Measurementsmentioning
confidence: 99%
“…20 Since the first observation of LAES, 25 the LAES experiments had been conducted using cw or long (≥ns) laser pulses 26 until our recent studies of femtosecond LAES experiments. 20,27 Probably because the major concerns in the previous LAES experiments were the scattering of slow electrons (≤76 eV) by rare gas atoms, 26 no experimental studies have been reported on the LAED of gas-phase molecules so far.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-assisted electron diffraction (LAED) 20 is a GED method we proposed in order to achieve the femtosecond temporal resolution. In the LAED method, we take advantage of a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Combining conventional electron or X-ray beam methods with femtosecond laser pulses provides improved temporal resolutions for molecular dynamics investigation approaching atomic time scales [23][24][25][26] . However, recent experiments [27][28][29][30][31] demonstrated that intense, isolated femtosecond pulses alone are sufficient for imaging simple molecules via a strong-field three-step process 32,33 (see Supplementary Discussion).…”
mentioning
confidence: 99%